A psychoeducational manual for counselling Alberta's aboriginal youth - Ladouceur, Christie-Dawn; University of Lethbridge. Faculty of Education (Lethbridge, Alta. : University of Lethbridge, Faculty of Education, c2013, 2013)
xiii, 175 leaves : ill. 29 cm The intent of this project is to provide helping professionals with the necessary knowledge required to provide culturally relevant counselling to Alberta’s urban Aboriginal youth. Aboriginal youth are the fastest growing demographic in Canada and represent almost half of the Aboriginal population. Because the issues facing Alberta’s urban Aboriginal youth are unique from those experienced by other non-dominant cultural groups in Alberta, providing culturally relevant and effective counselling to these clients can be a challenge. Presently counsellor training does not provide helping professionals with the necessary knowledge to deliver culturally relevant counselling to this at risk population. This manual will assist helping professionals in the development of their multicultural counselling skills by presenting a summary of Aboriginal history and rights, definitions of terminology, presenting issues experienced by this group, and information on cultural protocol and support systems.